Simulação do movimento vertical da água em área de recarga do Sistema Aquífero Bauru utilizando o software Hydrus-1D, em Araraquara - SP - Sacchi, Marcelo Donadelli [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Devido à crescente demanda por recursos hídricos subterrâneos para o abastecimento público, estudos sobre os mecanismos de recarga de aquíferos são fundamentais no detalhamento da capacidade de explotação dessas reservas. Nesse contexto, o Sistema Aquífero Bauru (SAB) representa uma das principais fontes de água subterrâneas do estado de São Paulo, com ocorrência também nos estados de Goiás, Minas Gerais, Paraná e Mato Grosso do Sul, perfazendo uma área total de aproximadamente 370.000 km2. Essa unidade hidrogeológica é constituída por rochas sedimentares do Grupo Bauru, que ocorre de forma extensiva e contínua por todo o Planalto Ocidental Paulista. Dados de precipitação, umidade e parâmetros físicos do solo foram utilizados para a construção de um modelo numérico de fluxo vertical da água em meio poroso em área de recarga do SAB. A aquisição desses dados ocorreu na cidade de Araraquara por um período de 366 dias, de 24 de março de 2019 até 24 de março de 2020, com o intuito de monitorar as condições atmosféricas do local e as propriedades físicas do solo na zona não-saturada do perfil estudado. Os dados relativos ao solo foram obtidos a partir das curvas de retenção e das curvas granulométricas, sendo utilizadas amostras deformadas e indeformadas, coletadas durante a escavação de um poço de monitoramento, no qual foram instalados sensores de umidade em diferentes profundidades. Como resultado da pesquisa, são apresentados os dados do monitoramento da variação temporal da umidade relativa do solo, além da distribuição granulométrica ao longo de um perfil de 6 metros, do potencial mátrico e da condutividade hidráulica vertical, utilizados na elaboração de um modelo numérico no software Hydrus-1D. O modelo permitiu simular, de maneira condizente, o volume de água que infiltrou pelo perfil de solo durante o período do monitoramento, confirmando a eficiência dos parâmetros do solo na determinação do movimento vertical da água.

An increase in exploitation of groundwater sources for public supply in São Paulo State in the past years, has brought the necessity of better understanding aquifers local recharge rate and exploitation capacity. The choice for Bauru Aquifer System (BAS) in this study is justified by its importance, being one of the main sources of groundwater in São Paulo, especially on the Western Plateau, where more than 70% of the municipalities depends partially or entirely on groundwater. BAS is an unconfined and sedimentary aquifer system, subdivided in smaller aquifers, which together sum up an extent of 370 000 km2 and is present in five Brazilian states. In this scenario, the study took place in the city of Araraquara - SP, in BAS recharge area, where atmospheric conditions and soil relative humidity were monitored for a period of 366 days, from March-24-2019 to March-24-2020, with few gaps. Also, a set of undeformed and deformed samples were gathered during the excavation of a monitoring well, which allowed the determination of the soil’s profile grain size distribution and retention curves for each sampled depth, which were used to set some of the model’s inputs. The well was installed in a plain recharge area, needed to setup soil moisture sensors in different depths of the soil profile. As a result, all data concerning soil physical properties, such as: the grain-size distribution over a 6-meter soil profile, its matric potential, hydraulic conductivity and soil’s humidity temporal variation is presented. In addition, the soil moisture temporal variation data allowed the calculation of the wetting front velocity, of 6cm/day, and shows the response of soil water for raining and drier periods in different depths. Consequently, these data were used to elaborate and calibrate a transient flow numerical model in Hydrus-1D, with the purpose of replicating infiltration rates and volumetric water content in the vadose zone of a porous soil profile, and although the model needed calibration, it’s first results already came up with a similar representation of the monitored conditions, which shows the efficiency of soil’s parameters for determining vertical water flow and estimating recharge rates. Also, a significant amount of data concerning water flow in the vadose zone for the study area is shown, which is useful for the acknowledgment of groundwater recharge processes in the Bauru Aquifer System.
Simulation of the vertical movement of water in the recharge area of ​​the Bauru Aquifer System using the Hydrus-1D software, in Araraquara - SP
Keywords: Geociências; Hidrogeologia; Sistema Aquífero Bauru; Águas subterrâneas; Recarga; SAB; Hydrus; Zona vadosa; Groundwater recharge; Unsaturated zone